INDIA'S CULTURAL RELATIONSHIP WITH ASIAN NATIONS - Ishfaq Ahmad Mir (CV. Radja Publika, 2023)
The social customs and technological advancements that have their roots in or are connected to the ethno linguistically heterogeneous country of India are known as Indian culture. The phrase also refers to nations and cultures outside of India whose histories have ties to India via immigration, colonialism, or other forms of influence, notably in South Asia and South-East Asia. An important chapter in the history of India is the spread of Indian culture and civilization to other regions of Asia. Indian trade relations with other nations date back many centuries. The spread of Indian languages, religions, arts, and architectural styles, as well as Indian philosophy, beliefs, and practices, was an inevitable outcome of this. In certain regions of Southeast Asia, Hindu kingdoms were even founded mainly through Indian political intrigue. The Indus Valley Civilization and other early cultural regions were influential in shaping Indian culture, which is sometimes described as a synthesis of various civilizations.